PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN BAHAN BANGUNAN PADA TB. SUMBER JAYA SERANG BANTEN - Steven Handoko; Ihwan Satria Lesmana; Ombi Romli (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Currently, it is not difficult to find shopping places that sell building materials at retail, both in big cities and in regions, both large and small scale. This has an impact on increasingly competitive competition between brick-and-mortar retail stores, so that as a result the traditionally managed brick-and-mortar retail business turns into an increasingly innovative, dynamic and competitive business. The aim of this research is to determine the partial and simultaneous influence of price and service quality on purchasing decisions for building materials in TB. Sumber Jaya, Serang City, Banten. The method used in this research is a survey method, using a quantitative correlational approach, namely looking at cause-and-effect relationships. The sample used was the entire population in this study, namely 66 respondents using the Tabachnick & Fidell sampling method. The results of the hypothesis testing research show that there is no influence between price on purchasing decisions, while other variables show that there is an influence between service quality on purchasing decisions. Likewise, simultaneously, there is an influence of price and service quality on purchasing decisions at TB. Sumber Jaya, Serang City, Banten, with an influential contribution of 34.9%, while the remaining 65.1% was influenced by other variables not discussed in this research.